Effect of Effective Microorganism-4 Probiotics in Drinking Water on Commercial Carcass Pieces of Male Bali DuckAged 8 Weeks - I K. E., Suprianto; Siti, N W.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
The study aimed to assess the weight and percentage of commercial carcass pieces of male bali duck aged 8 weeks given the Effective Microorganism-4 probiotic through drinking water was carried out in a cage belonging to Mr. I Ketut Sunatra located in Kediri, Tabanan, for 8 weeks. The study was carried out using a completely randomized design (CRD) consisting of three treatments, namely: T0 (drinking water without additional probiotics as a control), T1 (drinking water + probiotics 0.5%), and T2 (drinking water + probiotics 1%). Each treatment consisted of five replications and each replication used three male bali ducks aged 3 days with an average body weight of 55,72 ± 7.16 g. The variables observed were the weight and percentage of commercial carcasses pieces of the chest, upper thighs, lower thighs, wings, and back. The results showed that the administration of Effective Microoganism-4 probiotics through drinking water in the level of 1% significantly (P <0.05) increasing the weight of chest section by12.45%, the weight of the other carcass pieces were not significantly effect (P>0,05). The percentage of commercial carcass pieces also showed not significantly different (P> 0.05). Based on the results of the study it can be concluded that the administration of Effective Microorganism-4 probiotics through drinking water at the level of 0.5% and 1% can increase the weight of the commercial carcass pieces at the chest, but does not affect on the commercial carcass pieces of the upper thighs, lower thighs, wings and back of male bali ducks aged 8 weeks.  Keywords: Probiotic Effective Microorganism-4, male bali duck, commercial carcass pieces